2013
DOI: 10.1177/1045389x13476153
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological fluid composites synthesized for helicopter landing gear applications

Abstract: Magnetorheological fluid composites were formulated in this study to investigate their performance for potential use in landing gear hydraulic systems, such as shock struts. The magnetorheological fluids synthesized here utilized three hydraulic oils certified for use in landing gear, two average diameters of spherical magnetic particles, and a lecithin surfactant. The magnetorheology of these fluids was characterized, including (a) magnetorheology (yield stress and viscosity) as a function of magnetic field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
(22 reference statements)
0
19
1
Order By: Relevance
“…Numerous studies have identified the critical features of the MR damper, such as the controllable dynamic range of damping force, rapid adjustment response, and low energy consumption [1][2][3][4]. The initial implementation of the MR damper was in the automotive industry [5][6][7]; more recently, it has penetrated other sectors, including aerospace [8,9], marine structure [10], military [11,12], biomedical devices [13,14], home appliances [15], railway [16][17][18], and civil engineering [19][20][21]. The fundamental principle of the MR damper is similar to that of the conventional passive damper, which dissipates kinetic energy as heat through the flow restriction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified the critical features of the MR damper, such as the controllable dynamic range of damping force, rapid adjustment response, and low energy consumption [1][2][3][4]. The initial implementation of the MR damper was in the automotive industry [5][6][7]; more recently, it has penetrated other sectors, including aerospace [8,9], marine structure [10], military [11,12], biomedical devices [13,14], home appliances [15], railway [16][17][18], and civil engineering [19][20][21]. The fundamental principle of the MR damper is similar to that of the conventional passive damper, which dissipates kinetic energy as heat through the flow restriction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, elements of smart and functional materials have been added to the conventional composite structures to develop a new generation of the laminated composite structures [8]. Researchers have proposed and test many types of smart materials, including piezoelectric, shape memory alloys, fiber optics, and electrorheological (ER) and magnetorheological (MR) fluids, to add the required features, such as controllability, and improve the performance for specific applications [9][10][11][12][13][14]. These structures have the capability to adapt their response to external stimuli such as load or environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, some MREAs are generally used infrequently in impact mitigation applications. Such examples might be seismic dampers for earthquake mitigation system (Jiang and Christenson, 2012; Yang et al, 2002), energy absorbers for sliding seat system (Mao, 2011, Mao et al, 2007) or occupant protection system (Ahamed et al, 2014; Browne et al, 2004; Woo et al, 2007), lag dampers in helicopter (Mikułowski, 2008; Powell et al, 2013; Wereley et al, 2011), and shock absorbers for a gun recoil system (Li and Wang, 2012; Singh and Wereley, 2014). In these cases, the MRF, due to its sedimentation, could not maintain its original particle concentration for the entire period prior to its use (Choi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%